SUMBER KEUNGGULAN BERSAING BIDANG PRODUKSI OPERASIONAL DAN DAMPAKNYA PADA HASIL KINERJA PERUSAHAAN : Hasil Studi Empiris Pada Perusahaan Manufaktur di Indonesia. - fatiki Rahayu (Universitas Trisakti, 2001)
This study examines a model of the relationship among source of competitive advantage and performance outcomes. Production and operation competency is considered as a source of advantage. This competency is definedas the sum of the performanca on some production and operation competitive items, weighted by importance and extent of responsibility. Relationship between this competency contructs with performance outcomes such as ROl andmarket share are analyzed. The questinnaere were sent to production and operation managers. The instrument is used from Vickery et al. (1993), Elitan (1998). Regression was used to analysis data. The result shows there are positive relationship between production and operation competency with ROl and market share.